Enhanced sensitivity of laforin- and malin-deficient mice to the convulsant agent pentylenetetrazole - García-Cabrero, Ana M.; Sánchez-Elexpuru, Gentzane; Serratosa, José M.; Sánchez, Marina P. (Frontiers in Neuroscience, 2014)
Lafora disease is a rare form of inherited progressive myoclonus epilepsy caused by mutations in the EPM2A gene encoding laforin, or in the EPM2B gene, which encodes malin. It is characterized by the presence of polyglucosan inclusion bodies (Lafora bodies) in brain and other tissues. Genetically engineered mice lacking expression of either the laforin (Epm2a−/−) or malin (Epm2b−/−) genes display a number of neurological and behavioral abnormalities that resemble those found in patients suffering from Lafora disease; of these, both Epm2a−/− and Epm2b−/− mice have shown altered motor activity, impaired motor coordination, episodic memory deficits, and different degrees of spontaneous epileptic activity. In this study, we analyze the sensitivity of Epm2a−/− and Epm2b−/− mice to the convulsant drug pentylenetetrazol (PTZ), an antagonist of the γ-aminobutyric acid type A (GABAA) receptor, commonly used to induce epileptic tonic-clonic seizures in laboratory animals. PTZ-induced epileptic activity, including myoclonic jerks and tonic-clonic seizures, was analyzed in 2 age groups of mice comprising representative samples of young adult and aged mice, after administration of PTZ at sub-convulsive and convulsive doses. Epm2a−/− and Epm2b−/− mice showed a lower convulsive threshold after PTZ injections at sub-convulsive doses. A lower convulsive threshold and shorter latencies to develop epileptic seizures were observed after PTZ injections at convulsive doses. Different patterns of generalized seizures and of discharges were observed in Epm2a−/− and Epm2b−/− mice. Epm2a−/− and Epm2b−/− mice present an increased sensitivity to the convulsant agent PTZ that may reflect different degrees of increased GABAA receptor-mediated hyperexcitability.